The Effectiveness of Giving the COVID-19 Vaccine in Pregnancy - Nasriyah; Islami; Nor Asiyah (Urecol Journal. Part C: Health Sciences, 2021)
The period of pregnancy is very vulnerable to transmission of various kinds of viral infections, including the Corona Virus that is currently spreading in Indonesia. One of the efforts to prevent contracting the COVID-19 virus is the administration of the COVID-19 vaccine. The purpose of this study was to determine the effectiveness and safety of administering the COVID-19 vaccine during pregnancy. The method in this study uses a literature review of 17 journals or articles that discuss vaccines in pregnancy. Based on the results of a literature review from 17 articles related to the effectiveness and safety of the COVID-19 vaccine, it shows that vaccination in pregnancy can provide protection for the mother and fetus. In general, the vaccine does not cause growth and development disorders in the fetus, if given at least 12 weeks of gestation or entering the second trimester, Side effects after vaccination only have mild symptoms such as fever and pain at the injection site. The harmful side effects are unknown and still need further research. To increase the scope and target of COVID-19 vaccination, it is expected that health workers or health cadres will provide health counseling/education about the effectiveness and safety of the COVID-19 vaccine, the need for cross-sectoral collaboration and support from government officials in this case the health department.